Ayurvedic Management of Psoriasis: A Case Study (International Journal of Ayurveda and Pharma Research, 2022)
Skin, the body’s largest organ, protects from deleterious environmental impacts (physical, chemical, microbiological) and is crucial for the maintenance of temperature, electrolyte and fluid balance and tactile sensation, it sets a boundary between the organism and the environment. Any change in the normal skin texture disturb the patient both mentally and physically. Psoriasis is a common, chronic, recurrent inflammatory disease of the skin, characterized by circumscribed, erythematous, dry, scaly plaques of varying sizes. The severity of psoriasis is found to be ever fluctuating. Individuals are likely to cycle between differing levels of severity throughout lifetime. The course of the disease is punctuated by spontaneous flare-ups and remissions. Psoriasis being a chronic and often disfiguring condition, cause a marked impairment in quality of life. There is no certain cure for this disease. Ayurvedic diagnosis is as Vatha-Kapha predominant Mahakushta namely Sidhma kushta. Here an effort to treat a 13-year-old child having plaque psoriasis by Samsodhana and Samsamana therapy. Initially 6 days Virechana was performed and then followed by Samsamana with intermittent Virechana karma. PASI score is used to assess the severity of psoriatic lesions and the patient’s response to treatment. PASI score before the treatment was found to be 15.7 which became 0 at the end of the treatment. This case report showed the treatment modalities done in the patient obtained great result with no recurrence in the last 1.5 years.